Waqf-based crowdfunding model for islamic heritage conservation in Malaysia - Muhammad Shahrul Ifwat Ishak; Abdulmajeed Muhammad Aderemi (Penerbit Universiti Kebangsaan Malaysia, 2022)
This paper explores the potential of waqf-based crowdfunding as a means to obtain funds for conservation efforts related to Islamic heritage sites or materials in Malaysia. Over the period, several heritage sites, buildings, and materials, including Islamic heritage, have witnessed a lack of funding for conservation efforts, while the budget from the government is limited. Therefore, an alternative fund is needed, and Islamic crowdfunding has the potential to be applied to overcome this issue. This paper is based on conceptual explorations of literature on crowdfunding, waqf, and heritage conservation. As a result, its finding proposes a particular model of waqf-based crowdfunding fund for Islamic heritage conservation in this country. While several challenges are identified, including the potential failure to reach the target, and the lack of public awareness and approval from authorities, this study expands a new potential for the application of waqf. It provides a practical solution for Islamic heritage conservation in Malaysia.